2019
DOI: 10.4103/jcd.jcd_241_19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different obturating techniques and sealers on the removal of filling materials during endodontic retreatment

Abstract: Background: Adequate removal of previous root filling materials is an important objective during endodontic retreatment. Aim: This study was aimed to evaluate the influence of obturation quality and sealer type on the removal of root filling materials during endodontic retreatment using micro-computed tomography (μ-CT). Materials and Methods: Ninety extracted mandibular premolars were randomly assigned to two groups ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The ambiguity was resolved by discussion with a third reviewer and a total of 12 articles were selected for full-text reading. Out of these articles, 3 did not satisfy the inclusion criteria [72][73][74]. Reviewer agreement was absolute (k = 1).…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…The ambiguity was resolved by discussion with a third reviewer and a total of 12 articles were selected for full-text reading. Out of these articles, 3 did not satisfy the inclusion criteria [72][73][74]. Reviewer agreement was absolute (k = 1).…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…[ 20 ] The results of the present study also correlate with findings of another recent study wherein WVC has provided the highest percentage of root-filled area compared to injectable GP and LC and techniques. [ 21 ] As there was a significant difference in sealer penetration depth and adaptation observed for all the three groups, the null hypothesis was rejected based on the results of the present study.…”
Section: Discussionmentioning
confidence: 77%
“…[ 6 ] The findings of the present study revealed that no retreatment technique was found to be capable of completely removing the obturating material, which is in accordance with the previous studies. [ 7 8 9 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the technique used, the present study recorded greater remnants in the apical which may be explicated by the fact that both PTUR and NeoEndo-R system has a large taper, which is responsible for cutting more of coronal dentin. Furthermore, due to greater anatomical variations in the apical third region,[ 10 20 ] considerable enlargement is required for effective cleaning and shaping.…”
Section: Discussionmentioning
confidence: 99%